THE EFFECT OF BOARD CHARACTERISTICS, EARNINGS QUALITY, FIRM SIZE, AND PROFITABILITY ON FIRM VALUE - Dzikri, Muhammad Maftuh; Hasnawati Zainal (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2025)
This study aims to determine the effect of the characteristics of the board of commissioners, Earnings Quality, firm size, and profitability on firm value. The data for this study were collected through the Indonesia Stock Exchange and company websites. A total of 182 samples in this study came from 91 companies, with the research period being 2022-2023. The study results indicate that Firm size has a negative effect on firm value, profitability has a positive effect on firm value, board independence, board size, frequency of board meetings, board age, and earnings quality do not affect firm value.